Comradery and the Arts - Stuart Richards; Jessica Pacella; Kim Munro (Journal of Festive Studies)
This research is a result of the collaborative relationship between the Creative People, Products and Places (CP3) Research Centre at the University of South Australia and Festival City Adelaide (FCA). FA manages the consortium of South Australia’s eleven major arts and culture festivals. This report examines the current literature on volunteering in the arts sector and surveys the experiences of senior members of the Festival Volunteer Network, a platform managed by FCA that connects three thousand volunteers to the eleven festivals. In December of 2021 a survey was issued to the Festival Volunteer Network. Researchers received 176 responses (n=176). The survey was comprised of both qualitative and quantitative questions. The qualitative responses were coded thematically using NVivo software. Thematic coding was applied to each question separately. In order of recurrence in survey responses, the reasons why participants volunteered were for a more immersive festival experience, to connect with other volunteers, and to give back to the sector. Challenges to volunteering for senior patrons were finding the time to volunteer more, difficult patrons, and dealing with difficult festival managers. Skills learned while volunteering fell under the categories of festival management, event-related skills, customer service skills, and communication. Most senior volunteers maintained social contacts that they made while volunteering. This project builds upon existing research on volunteer labor at festivals and offers recommendations for improving volunteer management.